Higher orbital integrals, Shalika germs, and the Hochschild homology of Hecke algebras - Victor Nistor (International Journal of Mathematics and Mathematical Sciences)
We give a detailed calculation of the Hochschild and cyclic homology of the algebra 𝒞c∞(G) of locally constant, compactly supported functions on a reductive p-adic group G. We use these calculations to extend to arbitrary elements the definition of the higher orbital integrals introduced by Blanc and Brylinski (1992) for regular semi-simple elements. Then we extend to higher orbital integrals some results of Shalika (1972). We also investigate the effect of the induction morphism on Hochschild homology.